High Risk Pregnancy Screening for Pregnant Women - Fitri Ayatul Azlina; Rieh Firdausi; Nana Astriana Hasibuan; Azkalina Putri Dzulkaidah; Nada Tsuraya; Ananda Humaira Meidiani (Indonesian Journal of Global Health Research, 2026)
High-risk pregnancies lead to increased maternal mortality both globally and nationally and have negative impacts on both mothers and fetuses. The Maternal Mortality Rate (MMR) is one indicator in assessing the quality of health services. Screening for factors causing high-risk pregnancies is important. This study aims to identify high-risk pregnancies in pregnant women in the Karang Intan 2 Community Health Center area. This study used a descriptive analytical design with 51 respondents. Data collection was conducted from March to August 2025 with the sampling technique used was total sampling. This study used measuring instruments such as a blood pressure monitor, a glucometer, and a hemometer. Demographic data included age, education level, occupation, family income, gestational age, parity, ANC visits, medical history, abortion history, and premature birth history. Data were analyzed using univariate analysis to observe the frequency distribution of demographic data and measurement check up. The results showed that 49 (96.08%) respondents did not experience gestational hypertension, 41 (80.39%) respondents did not experience anemia, and all respondents did not experience gestational diabetes mellitus. Several other risk factors also influence the occurrence of pregnancy complications. Research shows that pregnant women are at high risk for increasing the occurrence of complications and dangers in pregnancy.